Chemically crosslinkable thermosensitive polyphosphazene gels as injectable materials for biomedical applications - Potta, Thrimoorthy; Chun, ChangJu; Song, Soo-Chang (ELSEVIER SCI LTD, 2009)
Chemically crosslinkable and thermosensitive poly(organophosphazenes) containing multiple thiol (-SH) groups along with hydrophobic isoleucine ethyl ester and hydrophilic alpha-amino-omega-methoxypoly(ethylene glycol) of the molecular weight 550 have been synthesized and characterized as an injectable biomaterial. The aqueous solutions of these polymers were transformed into hydrogel with desired gel strength at body temperature via hydrophobic interactions, and the gel strength was further improved by the cross-linking of thiol groups with crosslinkers, divinyl sulfone (VS) and PEG divinyl sulfone (PEGVS) under physiological conditions. The kinetics of cross-linking behavior of polymer thiol groups with crosslinkers was studied in both in vitro and in vivo conditions. Field Emission-Scanning Electron Microscopy (FE-SEM), swelling experiments, and rheology study of present polymers revealed that the inner three-dimensional hydrogel networks depended on the degree of thiol units in the polymer network. From the in vivo (in mice) degradation studies, the dual cross-linked gels showed to have a controlled degradation. These results demonstrate that the inner network of the hydrogels can be tuned, gel strength and degradation rate can be controlled, and the chemically crosslinkable and thermosensitive poly(organophosphazenes) hold promises for uses as injectable systems for biomedical applications including tissue engineering and protein delivery. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: PPO-PEO TRIBLOCKS; AMINO-ACID ESTERS; POLY(ETHYLENE GLYCOL); HYDROGELS; GELATION; POLY(ORGANOPHOSPHAZENES); POLYMERIZATION; DEGRADATION; POLYMERS; ADHESIVE